2001
DOI: 10.1038/sj.sc.3101210
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and predictive factors of therapeutic success with sildenafil for erectile dysfunction in patients with different spinal cord injuries

Abstract: Spanish Society of Paraplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
1
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 10 publications
3
43
1
2
Order By: Relevance
“…These results are in line with other randomized or placebo-controlled studies. 8,[10][11][12][14][15][16] The adverse effects of PDE5 inhibitors were mild in 6-15% of the patients. No episode of severe hypotension was experienced, probably because patients prone to blood pressure instability were excluded from this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in line with other randomized or placebo-controlled studies. 8,[10][11][12][14][15][16] The adverse effects of PDE5 inhibitors were mild in 6-15% of the patients. No episode of severe hypotension was experienced, probably because patients prone to blood pressure instability were excluded from this study.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, PDE5 inhibitors amplify the physiological NO/cGMP mechanism and reinforce the existing mechanical erection. 8,15 Home-based assessments showed that PDE5 inhibitors significantly improve the sexual life of SCI patients, particularly in the IIEF domains of erectile function, intercourse satisfaction and overall satisfaction for the three drugs. These results are in line with other randomized or placebo-controlled studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[6][7][8][13][14][15][16] In all these studies, sildenafil was reported to have notable efficacy for obtaining and maintaining an erection in patients with SCI. However, in many of these studies, 2,6,7 patients with neurological levels of SCI above T5 were systematically excluded due to the potential risk of autonomic dysreflexia and, especially, of hypotension. Similarly, many of the studies excluded individuals with hypotension (systolic/diastolic blood pressure o90/50 mmHg, respectively).…”
Section: Introductionmentioning
confidence: 98%
“…In total, 80% of these patients have some type of erection, either reflex, psychogenic or mixed. 2 However, most of these erections are inadequate to engage in satisfactory sexual contacts and usually require some type of therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%